The implications of palm cooking oil price increases in Malaysia - Abdullah Chik, Norlaila; Farha Alias, Emmy; Mohammad Ali, Siti Asmahan; Sulaiman, Noorasiah (Universiti Putra Malaysia, 2023)
Domestic palm oil consumption in Malaysia increased to about 3.37 million metric tons in 2022. This number is expected to increase further due to population growth and consumer preferences for palm oil cooking oil. However, in 2016, the government withdrew its subsidy on palm cooking oil, increasing its price by 48.9%. Recently, the government proposed to use a floating price for palm cooking oil. These changes have left direct and indirect impacts on food producers and consumers. Therefore, this paper examines the impact of an increase in the price of palm cooking oil on food producers (directly) and consumers (indirectly). This study applied the Leontief price modelling technique and simulated a scenario for the price changes in the production cost. The simulation results indicated that costs and prices changed. The results found that the most significant cost change came from restaurants, 52.0%, while other price changes were from oil palm (29.6%) and restaurants (17.4%). This study also used the profit index to calculate the profit food producers and services gained. Based on this scenario, food producers should revise their prices of goods and services since they still gain profit. It was recommended that the government revise the price of palm cooking oil by providing subsidies or incentives to the food producer or consumer. The fluctuation in palm oil prices impacts the price of palm cooking oil in the market. If the government does not revise cooking oil prices, it will affect food consumers and producers.